Nanobiomaterials-Based Environmental Bioremediation: A Special Focus on Microplastics - Sekar R.; Das S.; Shirin S.; Srinivasan R.; Marimuthu P.; Atchuthan P.; Amith S.L.; Somu P.; Yadav A.K. (My University, 2025)
Environmental pollution by microplastics (MPTs) generated by physical destruction of plastics is a global problem with enduring and biohazardous threats. In recent decades, the expulsion of MPTs from the environment has affected human health and the green atmosphere. Currently, several significant high-tech innovations have been designed and reported to clean dangerous MPTs. Among them, nanotechnology-based biomaterials have received potential attention for bioremediation. This chapter focuses on collective microbial power technologies (MPTs) present in the natural green environment and explores techniques utilizing bionanomaterials for their effective cleaning. It is also providing information on bioremediation and designing modern green-environment approaches to control and purge MPTs in a short time. Moreover, we describe the different techniques with their advantages and disadvantages, which are also discussed. Finally, we conclude with the future outlook for delivering the path to a complete purge of MPTs. © 2024 American Chemical Society.